Mucor as a cause of surgical site infection. (July 2020) - Negi, Ravikanta; Kaushik, Robin; Singh, Simrandeep; Punia, Rajpal Singh
Mucor is an uncommon cause of surgical site infection. We present such a case after intramedullary nailing of the femur and discuss its presentation and management.